Surgical Risk Factors for Ischemic Stroke Following Coronary Artery Bypass Grafting. A Multi-Factor Multimodel Analysis - Gelsomino, Sandro; Tetta, Cecilia; Matteucci, Francesco; del Pace, Stefano; Parise, Orlando; Prifti, Edvin; Dokollari, Aleksander; Parise, Gianmarco; Micali, Linda Renata; La Meir, Mark; Bonacchi, Massimo (Frontiers in Cardiovascular Medicine, 2021)
Background. Ischemic stroke after coronary artery bypass (CABG) has been often linked to aortic manipulation during surgery. Objectives. The objective of the study was to estimate the rate of postoperative ischemic stroke within 30 days from CABG by surgical risk factors alone or in combination. Methods The multinomial propensity score for multiple treatments was used to create six models with a total of 16255 consecutive patients undergoing isolated CABG. For each model, a different classification variable was used to stratify patients. Results Balance achieved in all models was substantial, enabling unbiased estimation of the treatment estimand. Both off-pump techniques with (0.009; 95% CI 0.006-0.011) or without proximal anastomoses (0.005; 0.005-0.003), and surgery performed on the beating heart using cardiopulmonary bypass with (0.009; 0.006-0.011) or without proximal anastomoses (0.024;0.021-0.029) showed a mean stroke estimate significantly lower than the other techniques. Off-pump surgery and on-pump surgery without an aortic cross-clamp yielded nearly equal incidences of stroke (0.012;0.008-0.015 and 0.018;0.012-0.023, respectively). Using an aortic cross-clamp significantly increased the stroke estimate (0.075; 0.061-0.088), whereas using a side-biting clamp did not (0.039;0.033-0.044). The number of aortic touches (0.029;0.026-0.031) and the number of proximal anastomoses (0.044; 0.035-0.047) did not significantly increase the incidence of stroke. Conclusions. Aortic cross-clamping was found to be the primary cause of post-CABG ischemic stroke. Instead, additional aortic manipulation from a side-biting clamp, on-pump surgery, multiple aortic touches, number of proximal anastomoses, and aortic cannulation were found not to increase the estimate of stroke significantly. Further research on this topic is warranted.